Effect of polystyrene modifier on the properties of polyvinylchloride plasticates - Laruk, Yuriy; Levytskyj, Volodymyr; Huminetsky, Taras; Sikora, Janusz (Видавництво Львівської політехніки, 2013)
Polyvinyl chloride plasticates have been modified including the preliminary dissolution of polystyrene modifier in diesterphthalate plasticizer followed by combination with dispersed polyvinyl chloride. The effect of modifier and plasticizer natures on the wetting of polyvinyl chloride by plasticizer has been studied and grounded. The degree of plasticizer migration out of matter volume and its influence on elastic-plastic, strength and thermo-physical properties of modified materials have been determined.
Keywords: polyvinyl chloride; migration; plasticization; modification; polystyrene; ABS plastic